Occupational Health & Safety Management Systems - When are they good for your health? - Kempa, Viktor; Frick, Kaj (Brussels, 2011)
"In the course of trade union debates, occupational health and safety management systems elicit extremely varied responses, running from indignant rejection to enthusiasm. Understandably, because the term "is used to describe all kind of practices. It can cover anything from ambitious continuous improvements towards the utopian goal of no health risks at work, to corporate smokescreens for con*trolling workers and busting unions", caution Kaj Frick (Mälardalen University) and Viktor Kempa (ETUI) in the opening lines of the report. The report surveys this booming "market", distinguishing management systems devised by private firms from those promoted by national authorities, the best known and most controversial being the US Voluntary Protection Program. The authors nevertheless stress that the type of management system is less important than how it is interpreted and put into practice in workplaces. Specifically, they demolish the argument that mandatory (public) management systems are inherently good and optional (usually private) management systems are automatically bad. But much as they may prompt employers to engage with health and safety at work, the authors take issue with these management systems for "seeming to look more for accident risks than for long-term health risks"."